2007
DOI: 10.1111/j.1365-3083.2007.02034.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Qa1b in the Protection of Mature Dendritic Cells from NK Cell‐Mediated Killing

Abstract: Molecular interactions in natural killer (NK) cell‐mediated killing of dendritic cells (DC) have under recent years come under scrutiny. Upon stimulation with IFN‐γ or lipopolysaccharide, DC become relatively resistant to NK cell‐mediated lysis. In the present study, we investigated the role of Qa1b on DC and its receptor NKG2A on NK cells in the protection of mature DC from NK cells. We demonstrate that while both NKG2A+ and NKG2A‐ NK cells can efficiently lyse unstimulated DC, NKG2A+ NK cells but not NKG2A‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…, signals transmitted by inhibitory receptors for MHC class I molecules inhibited NK cell-mediated cytolysis [1], [2]. Recent studies have demonstrated that Qa-1b is critically involved in regulating IFN-γ synthesis by NK cells as a result of interactions with the CD94/NKG2A inhibitory receptors that may protect DC from NK cell-mediated cytolysis even in the absence of classical MHC class I molecules [11], [24]. To address whether Qa-1 was also critical in protecting murine macrophages from NK cell-mediated killing, we first compared the expression level of Qa-1 mRNA in poly I:C-treated or untreated macrophages (RAW264.7 cells and peritoneal macrophages freshly isolated from BALB/c mice) and found no significant changes in the Qa-1a and Qa-1b transcript levels following poly I:C stimulation, but the levels of Qa-1a in poly I:C-treated or untreated primary macrophages are much higher than that in YAC-1 cells by 16.7±1.98 folds and 16.9±0.97 folds separately, and the levels of Qa-1b in primary macrophages are higher by about 10 folds (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, signals transmitted by inhibitory receptors for MHC class I molecules inhibited NK cell-mediated cytolysis [1], [2]. Recent studies have demonstrated that Qa-1b is critically involved in regulating IFN-γ synthesis by NK cells as a result of interactions with the CD94/NKG2A inhibitory receptors that may protect DC from NK cell-mediated cytolysis even in the absence of classical MHC class I molecules [11], [24]. To address whether Qa-1 was also critical in protecting murine macrophages from NK cell-mediated killing, we first compared the expression level of Qa-1 mRNA in poly I:C-treated or untreated macrophages (RAW264.7 cells and peritoneal macrophages freshly isolated from BALB/c mice) and found no significant changes in the Qa-1a and Qa-1b transcript levels following poly I:C stimulation, but the levels of Qa-1a in poly I:C-treated or untreated primary macrophages are much higher than that in YAC-1 cells by 16.7±1.98 folds and 16.9±0.97 folds separately, and the levels of Qa-1b in primary macrophages are higher by about 10 folds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD94/NKG2A is one of the major inhibitory receptors in mice, and it recognizes the non-classical major histocompatibility complex (MHC) molecules Qa-1 that is expressed by most cell types. It has been suggested that the Qa-1-CD94?NKG2A interaction is critical for preventing NK cell-mediated killing of mature dendritic cells (DCs) [10], [11]. Therefore, the actions of NK cells are thought to be mediated by the complex interactions between inhibitory and activating signals sent by cell surface receptors following ligation.…”
Section: Introductionmentioning
confidence: 99%
“…DC are sensitive to NK cellmediated lysis in vitro and can be eliminated by NK cells in vivo (4,6,17,19,33,43). Viral or bacterial infection of DC can reduce their sensitivity to NK cell-mediated lysis by increasing the expression of classical and nonclassical major histocompatibility complex class I molecules on the cell surface (14,35,43).…”
mentioning
confidence: 99%
“…In addition, pDC secrete several chemokines, including CCL3, CCL5, and CXCL10, at levels higher than cDC of myeloid origin [30,[33][34][35]. NK cells can interact, directly or indirectly, with DC [4,5,[36][37][38][39][40][41][42][43][44][45]. For example, the activation of DC by pathogens leads to cytokine secretion, which activates NK cells, which in turn may affect the subsequent adaptive immune responses, either via cytokines or by direct cell-cell contact [5,6,46].…”
Section: Introductionmentioning
confidence: 99%